Analisis Minat Belajar Siswa SMP Taman Siswa Malang Terhadap Keanekaragaman Tumbuhan - Yenisari Mone, Yasinta; Hindun, Nurmala (Universitas Insan Budi Utomo, 2024)
Indonesia is a vast archipelagic country, with a very high level of flora and fauna diversity, so it is called a megabiodiversity country. Indonesia is estimated to have 90 types of ecosystems, both land and water, and there are 15 natural forest formations that have high productivity. The largest natural forest formation in Indonesia stretches from the western tip from Sabang to the eastern tip with a diversity of animal and plant species, and is supported by its geographical location in the tropics with a unique climate. Utilizing the surrounding environment as a learning tool makes learning more interesting and contextual. Learning with the help of the surrounding environment can support the student's development process as a whole, because it is directly related to cognitive, effective and psychomotor aspects. So, with the environment as a means of teaching and learning. This research aims to analyze the learning interest of Taman Siswa Malang Middle School students in science subjects, especially the topic of plant diversity. This research used a quantitative descriptive approach involving 35 class VII students as the population and research sample. Data was collected through an open interest questionnaire with the Guttman scale and analyzed descriptively. The research results showed that students' interest in learning science subjects at Taman Siswa Middle School Malang was relatively high, with an average score of 79.48%. The indicators of learning interest studied include feelings of enjoyment, interest, attention and involvement. Students show high feelings of enjoyment towards science lessons, with an average score of 90.29%. The interest indicator has an average score of 73.33%. the attention indicator has an average score of 82.86% showing a high score and the engagement indicator has an average score of 71.41%. With these results, it can be seen that the lowest indicator is the engagement indicator.